An Adaptive Moving Mesh Method for the Five-Equation Model (Communications in Computational Physics, 2022)
The five-equation model of multi-component flows has been attracting muchattention among researchers during the past twenty years for its potential in the studyof the multi-component flows. In this paper, we employ a second order finite volume method with minmod limiter in spatial discretization, which preserves local extrema of certain physical quantities and is thus capable of simulating challenging testproblems without introducing non-physical oscillations. Moreover, to improve thenumerical resolution of the solutions, the adaptive moving mesh strategy proposedin [Huazhong Tang, Tao Tang, Adaptive mesh methods for one- and two-dimensionalhyperbolic conservation laws, SINUM, 41: 487-515, 2003] is applied. Furthermore, theproposed method can be proved to be capable of preserving the velocity and pressure when they are initially constant, which is essential in material interface capturing.Finally, several classical numerical examples demonstrate the effectiveness and robustness of the proposed method.